2016
DOI: 10.1021/acsnano.5b06529
|View full text |Cite
|
Sign up to set email alerts
|

Few-Layer MoS2 p-Type Devices Enabled by Selective Doping Using Low Energy Phosphorus Implantation

Abstract: P-type doping of MoS2 has proved to be a significant bottleneck in the realization of fundamental devices such as p-n junction diodes and p-type transistors due to its intrinsic n-type behavior. We report a CMOS compatible, controllable and area selective phosphorus plasma immersion ion implantation (PIII) process for p-type doping of MoS2. Physical characterization using SIMS, AFM, XRD and Raman techniques was used to identify process conditions with reduced lattice defects as well as low surface damage and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
312
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(341 citation statements)
references
References 35 publications
18
312
0
Order By: Relevance
“…Currently, there is argument on the conductivity of undoped MoS 2 . The majority of recent studies of undoped MoS 2 conductivity report n-type behavior, 2,8,9,[12][13][14][37][38][39][40] and the previous studies revealed that the Fermi-level tends to be pinned at charge neutrality level or sulfur vacancy level which is located below the conduction band edge, so electrons are injected, thus making MoS 2 conductivity mostly n-type. 37 Furthermore, MoS 2 transistors are essentially Schottky barrier transistors, and thus the charge injection from the source electrode degrades the transistor output.…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there is argument on the conductivity of undoped MoS 2 . The majority of recent studies of undoped MoS 2 conductivity report n-type behavior, 2,8,9,[12][13][14][37][38][39][40] and the previous studies revealed that the Fermi-level tends to be pinned at charge neutrality level or sulfur vacancy level which is located below the conduction band edge, so electrons are injected, thus making MoS 2 conductivity mostly n-type. 37 Furthermore, MoS 2 transistors are essentially Schottky barrier transistors, and thus the charge injection from the source electrode degrades the transistor output.…”
Section: -mentioning
confidence: 99%
“…Besides, the MoS 2 film is fully covered on the substrate, and there is no edge of the body at the current path along with the four electrodes. The metal contact lies on top of the MoS 2 layers, then the current path may be limited by tunneling through the van der Waals gap, the surface exhibits intrinsic defects such as sulfur vacancy and ambient interactions such as physical or chemical absorption 12 result in strong n-type behavior can be detected in MoS 2 vdP measurements. Besides, the metallic character of sulfur vacancies can effectively lower Schottky barrier height 40 the I-V characteristics as shown in Fig.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…The drain–source current is controlled by the gate voltage on the dielectric layer. High carrier mobility, high switching ratio and low subthreshold swing means high performance FET, which depends on the metal contacts,247 channel materials (thickness,248, 249 doping,192, 250, 251, 252, 253, 254 heterostructures200, 208), dielectric materials (back‐gate,86, 255 top‐gate,256 liquid gate257), and so forth. 2D GIVMCs based FETs have demonstrated exciting performance.…”
Section: Device Applicationsmentioning
confidence: 99%
“…Despite this difficulty, Nipane et al have recently reported the successful p-doping of MoS 2 with phosphorous using plasma immersion ion implantation (PIII), where the MoS 2 is exposed to a phosphine plasma and bias of 0 eV, 1 keV, or 2 keV is applied to the sample to induce implantation. 5 While plasmas offer benefits such as a wide range of dopant species through different plasma chemistries, it's noted that the plasmas can bring numerous processing difficulties including undesired etching of the MoS 2 , imprecise dose control, and degradation of photoresist masks that are used for selective-area doping.…”
mentioning
confidence: 99%